Do Horses Expect Humans to Solve Their Problems? - Lesimple, Clémence; Sankey, Carol; Richard, Marie-Annick; HAUSBERGER, Martine (Frontiers in Psychology, 2012)
Domestic animals are highly capable of detecting human cues, while wild relatives tend to perform less well (e.g. responding to pointing gestures). It is suggested that domestication may have led to the development of such cognitive skills. Here, we hypothesized that because domestic animals are so attentive and dependant to humans’ actions for resources, the counter effect may be a decline of self sufficiency, such as individual task solving. Here we show a negative correlation between the performance in a learning task (opening a chest) and the interest shown by horses towards humans, despite high motivation expressed by investigative behaviours directed at the chest. If human-directed attention reflects the development of particular skills in domestic animals, this is to our knowledge the first study highlighting a link between human-directed behaviours and impaired individual solving task skills (ability to solve a task by themselves) in horses.